Genetic Variants at the IFNL3 Locus and Their Association with Hepatitis C Virus Infections Reveal Novel Insights into Host-Virus Interactions - Chinnaswamy, Sreedhar (Mary Ann Liebert, Inc., 2014)
Human genetic variation plays a critical role in both spontaneous clearance of and response to interferon (IFN)-based therapies against hepatitis C virus (HCV) as shown by the success of recent genome-wide association studies (GWAS). Several GWAS and later validation studies have shown that single nucleotide polymorphisms (SNPs) at the IFNL3 (formerly IL28B) locus on chromosome 19 are involved in eliminating HCV in human patients. No doubt that this information is helping clinicians worldwide in making better clinical decisions in anti-HCV therapy, but the biological mechanisms involving the SNPs leading to differential responses to therapy and spontaneous clearance of HCV remain elusive. Recent reports including the discovery of a novel IFN (IFN-λ4) gene at the IFNL3 locus and in vitro functional studies implicating 2 SNPs as causal variants lead to novel conclusions and perhaps to new directions in research. An attempt is made in this review to summarize the major findings of the GWAS, the efforts involved in the discovery of causal SNPs; and to explain the biological basis for spontaneous clearance and response to treatment in HCV infections.